Changes in children’s wellbeing in Bradford during COVID-19: The Born in Bradford COVID-19 longitudinal research study [version 2; peer review: 2 approved] - Brian Kelly; Bo Hou; Mildred Ajebon; Katie Pybus; Rosemary McEachan; Claire McIvor; Kate E. Pickett; Josie Dickerson; Daniel Bingham (Wellcome Open Research, 2022)
Background: Concerns have been raised about the potential impact of COVID-19 and associated lockdown measures on child mental wellbeing, but emerging evidence suggests mixed results and there is a dearth of information from ethnically diverse samples. The current study aims to explore the impact of the pandemic on wellbeing using longitudinal data collected from the multi-ethnic Born in Bradford family cohort study. Methods: Within-child changes in wellbeing were explored using data collected pre-pandemic and again during the first UK lockdown for 500 children aged 7-13 from a range of ethnic and socioeconomic backgrounds, using self-reported feelings of happiness and sadness. Associations between changes in wellbeing, demographic factors, quality of social relationships and physical activity levels were explored using multinomial logistic regression models. Results: In this sample, 55% of children reported no change in their wellbeing from pre-pandemic to during the first lockdown (n=264). Children of Pakistani heritage were more than twice as likely to report feeling sad less often than White British children (RRR: 2.61, 95% CI: 1.23, 5.51) during the first lockdown. Those who reported being left out by other children before the pandemic were over three times as likely than those who did not (RRR: 3.72: 1.51, 9.20) to report feeling sad less often during the pandemic. Around a third of children reported feeling happier (n=152, 31.6%), but these changes did not relate to any of the explanatory variables included in this analysis. Conclusion: Many children in this study reported no changes in their wellbeing during the first UK lockdown compared to before the pandemic and some described improved wellbeing. These findings suggest that children have coped well with the significant changes over the past year, though targeted support, particularly for those children who felt excluded before the pandemic, would be beneficial.